Validity of instrument to measure mathematics teachers’ perceptions towards 4C skills in problem solving - Zakaria, Mohamad Ikram; Noor Nasran, Nik Abdul Hadi; Abdullah, Abdul Halim; Alhassora, Najua Syuhada Ahmad; Hanid, Mohd Fadzil Abdul (Institute of Advanced Engineering and Science, 2024)
In the contemporary education 4.0 landscape, teachers are urged to prioritize the communication, collaboration, critical thinking, and creativity (4C) skills during teaching and learning, recognized as crucial skills for the 4.0 industrial revolution (I.R 4.0). This research aimed to develop and validate an instrument assessing mathematics teachers' perceptions of the 4C skills through problem-solving teaching method. Employing a quantitative research design, the study utilized a questionnaire for data collection, involving four experts and 120 participants. Descriptive analysis using Cronbach's alpha and exploratory factor analysis (EFA) revealed a high reliability (Cronbach's alpha=0.934) and factor eigenvalue exceeding 1. The KMO values (Kaiser–Meyer–Olkin) for each construct were 0.50, and Bartlett's Test was significant (<0.5). Additionally, each item demonstrated a factor loading value above 0.50 and a variance percentage of ≥60%. The instrument comprised 4 sub-constructs and 16 fitting items. In summary, the study affirms the utility of this instrument in investigating mathematics teachers' perceptions of 4C skills through problem-solving teaching methods.